(untitled) (Research, Society and Development, 2023)
Introduction: The term "oral cancer" encompasses a series of neoplasms that affect the oral cavity. Squamous cell carcinoma (SCC) is the most common type of malignant oral cancer, accounting for more than 90% of all malignant tumors in this region. Tumors located in the soft palate and oropharynx are usually larger in size compared to carcinomas that affect the lips and tongue. Surgical treatment is the most indicated option for this pathology, although it can be aggressive, affecting adjacent oral structures, especially when it involves the most posterior areas. This surgical approach can result in functional disorders, such as speech, chewing and swallowing difficulties. Objective: This paper aims to report a case of oral rehabilitation of a patient undergoing cancer treatment after being diagnosed with squamous cell carcinoma. The patient underwent surgical procedures, including radical left neck dissection, palate tumor resection, pelveglossomandibulectomy, pharyngeal resection, and brachial skin graft. Final considerations: A multidisciplinary approach is essential to restore the patient’s quality of life after cancer treatment. The dental surgeon plays a fundamental role in minimizing the consequences caused by the treatment. The manufacture of an obturator prosthesis generally allows satisfactory functional and aesthetic rehabilitation, without the need for additional invasive procedures.